2008
DOI: 10.1186/1477-7819-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Application of light microscopical and ultrastructural immunohistochemistry in the study of goblet cell carcinoid in the appendix

Abstract: Background: Goblet cell carcinoids appear less frequently in the appendix than do other carcinoids. In the presented work a case with a goblet cell carcinoid of the appendix is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Ultrastructural immuno- histiochemistry staining has shown tumor nests resembling normal crypts in the submucosa. Separate goblet cell and neuroendocrine cells are often located in close proximity to each other[24] (Table 1). …”
Section: Immunochemistry and Mutational Findingsmentioning
confidence: 99%
“…Ultrastructural immuno- histiochemistry staining has shown tumor nests resembling normal crypts in the submucosa. Separate goblet cell and neuroendocrine cells are often located in close proximity to each other[24] (Table 1). …”
Section: Immunochemistry and Mutational Findingsmentioning
confidence: 99%
“…However, the pattern of positivity is focal and patchy, unlike that in carcinoid tumors, where it is strong and diffuse [17] . Bombesin, endorphin, gastrin and secretin were found to be negative [29] . S100, Leu7 (CD57) and NCAM (CD56) staining around tumor cell nests is usually not identified in these tumors (unlike carcinoids) [8] .…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The granules contain chromogranin reaction products, and originating from ovoid or discoid EC2 type and D type, and are som etimes difficult to find [24,29] . Table 1 highlights the clinical and pathological dif ferences between GCC, typical carcinoid tumor and adeno carcinoma of the appendix.…”
Section: Electron Microscopymentioning
confidence: 99%
“…They were focally positive for chromogranin B and synaptophysin. However 5% to 25% of cases were entirely negative for neuroendocrine markers [7][8][9][10][11]. Immunohistochemical studies of this case revealed positive staining with antibodies against CKAE1/AE3, CK20, focal positive staining with antibody against chromogranin B.…”
Section: Discussionmentioning
confidence: 92%